Apareamiento, espermatóforo y aparato del dardo de Polymita brocheri (Gastropoda: Cepolidae): conducta y morfología. - Reyes-Tur, Bernardo; Gordillo-Pérez, Mario J.; Bosch-Diaz, Camila; Rodríguez-Potroní, Henry; Rodríguez-Matos, Juannier (Cuban Journal of Biological Sciences / Revista Cubana de Ciencias Biológicas)
Polymita brocheri (Cepolidae) is a hermaphroditic, threatened Cuban endemic tree snail, whose mating behavior has never been studied. Here, we described the mating behaviour and the use of the dart apparatus of P. brocheri, in captivity, and discussed the functional morphology of the dart apparatus and the spermatophore. The study was conducted between 2012 and 2018. Twenty-five adult individuals were collected in Maisí, Guantánamo and other seven individuals were obtained from a captive breeding colony. Individuals were kept isolated in plastic containers between 15 and 30 days before the mating sessions. Mating duration averaged 208 min and consisted of three stages: courtship, copulation and post-copulation. On average, courtship lasted 30 min, and included tactile contacts and semicircular movements. Copulation started simultaneously and lasted on average 105 min. During this stage took place the reciprocal exchange of spermatophores. The spermatophore was formed by three regions: neck, body and tail, with spines of different sizes in the neck and body. We suggested that spines might slow down spermatophore uptake into the bursa copulatrix. Post-copulation average was 76 min; penis withdrawal settled the beginning of this stage. Post-copulatory activity was characterized by semicircular movements. During all mating stages, three uses of the dart apparatus were distinguished: wiping, rubbing and stabbing, all of which were mainly directed toward the anterior region of the partner's body, usually without loss of the dart. The dart apparatus consists of several types of tissues and the accessory mucous glands possess abundant secretory cells. The low frequency of stabbing, as well as the presence of cylindrical epithelium and mucus in the atrial sac, suggest a key role of wiping and rubbing in order to transfer accessory gland products.